선행 줄기 세포 이식을 받은 환자에서의 T 세포 요법 - RYTLEWSKI JULIE ANN; MASHADI HOSSEIN AFSHIN; CAMPBELL TIMOTHY; FULLER JAYMES (2023)
종양 또는 암 (예컨대 B 세포 관련 암, 예를 들어 다발성 골수종)을 치료하기 위한 T 세포, 예를 들어 키메라 항원 수용체 (CAR) T 세포의 용도가 본원에 제공되며, 여기서 치료될 대상체는 이전에 줄기 세포 이식을 받았다. Provided herein are uses of T cells, e.g., chimeric antigen receptor (CAR) T cells, for treating a tumor or a cancer (such as B cell related cancer, e.g., multiple myeloma) wherein the subject being treated has previously received a stem cell transplant.